Analysis of the laccase gene family and miR397-/miR408-mediated posttranscriptional regulation in Salvia miltiorrhiza - Caili Li; Dongqiao Li; Hong Zhou; Jiang Li; Shanfa Lu (PeerJ, 2019)
Salvia miltiorrhiza is one of the most commonly used traditional Chinese medicine materials. It contains important bioactive phenolic compounds, such as salvianolic acids, flavonoids and anthocyanins. Elucidation of phenolic compound biosynthesis and its regulatory mechanism is of great significance for S. miltiorrhiza quality improvement. Laccases (LACs) are multicopper-containing enzymes potentially involved in the polymerization of phenolic compounds. So far, little has been known about LAC genes in S. miltiorrhiza. Through systematic investigation of the whole genome sequence and transcriptomes of S. miltiorrhiza, we identified 65 full-length SmLAC genes (SmLAC1–SmLAC65). Phylogenetic analysis showed that 62 of the identified SmLACs clustered with LACs from Arabidopsis and Populus trichocarpa in seven clades (C1–C7), whereas the other three fell into one S. miltiorrhiza-specific clade (C8). All of the deduced SmLAC proteins contain four conserved signature sequences and three typical Cu-oxidase domains, and gene structures of most LACs from S. miltiorrhiza, Arabidopsis and P. trichocarpa were highly conserved, however SmLACs encoding C8 proteins showed distinct intron-exon structures. It suggests the conservation and diversity of plant LACs in gene structures. The majority of SmLACs exhibited tissue-specific expression patterns, indicates manifold functions of SmLACs played in S. miltiorrhiza. Analysis of high-throughput small RNA sequences and degradome data and experimental validation using the 5′ RACE method showed that 23 SmLACs were targets of Smi-miR397. Among them, three were also targeted by Smi-miR408. It suggests the significance of miR397 and miR408 in posttranscriptional regulation of SmLAC genes. Our results provide a foundation for further demonstrating the functions of SmLACs in the production of bioactive phenolic compounds in S. miltiorrhiza.